Bali chef community's commitment to balinese gastronomy - Moch Nur Efendi (Universitas Merdeka Malang, 2024)
The purpose of this study was to determine the obstacles and contributions of the Bali Chef Community (BCC) in maintaining and advancing Balinese cuisine, while the qualitative descriptive method was used in this study. The data collection techniques used were interviews, observations and documentation. The results showed that there were obstacles in the form of regional attitudes, uneven culinary development and the absence of standard culinary recipes in each region. The contributions that have been made by BCC include 1) Making a traditional Balinese culinary book entitled